Thyroidectomy for Painful Thyroiditis Resistant to Steroid Treatment: Three New Cases with Review of the Literature - Enrico Mazza; Francesco Quaglino; Adolfo Suriani; Nicola Palestini; Cristina Gottero; Renzo Leli; Stefano Taraglio (Case Reports in Endocrinology)
Thyroidal pain is usually due to subacute thyroiditis (SAT). In more severe forms prednisone doses up to 40 mg daily for 2-3 weeks are recommended. Recurrences occur rarely and restoration of steroid treatment cures the disease. Rarely, patients with Hashimoto’s thyroiditis (HT) have thyroidal pain (painful HT, PHT). Differently from SAT, occasional PHT patients showed no benefit from medical treatment so that thyroidectomy was necessary. We report three patients who did not show clinical response to prolonged high dose prednisone treatment: a 50-year-old man, a 35-year-old woman, and a 33-year-old woman. Thyroidectomy was necessary, respectively, after nine-month treatment with 50 mg daily, two-month treatment with 75 mg daily, and one-month treatment with 50 mg daily. The two women were typical cases of PHT. Conversely, in the first patient, thyroid histology showed features of granulomatous thyroiditis, typical of SAT, without fibrosis or lymphocytic infiltration, typical of HT/PHT, coupled to undetectable serum anti-thyroid antibodies. Our data (1) suggest that not only PHT but also SAT may show resistance to steroid treatment and (2) confirm a previous observation in a single PHT patient that increasing prednisone doses above conventional maximal dosages may not be useful in these patients.